Pengaruh Laba Bersih, Arus Kas Bebas, Dan Arus Kas Operasi Terhadap Dividen Tunai Pada 12 Perusahan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (Periode 2012-2018) - Ardinal Djalil (Ekonam: Jurnal Ekonomi, Akuntansi & Manajemen, 2019)
Abstract : Cash Dividends are the most common type distributed by companies to shareholders. Because cash dividends help reduce the risk of uncertainty in shareholder investment activities. And for companies dividend payments can be used to strengthen the company's position in finding additional funds in the capital market. In determining the amount of dividends to be distributed by management is often faced with a difficult decision. This difficulty is caused by management having to consider paying dividends that are smaller, larger, permanent or stable, because any decision on dividend payments will result in investors acting on the company's shares. This study aims to analyze the effect of net income, free cash flow and operating cash flow on cash dividends. Data was obtained from companies listed on the Indonesian stock exchange in the period 2010-2016. This research uses descriptive verification research method. The independent variables in this study are Net Income (X1), Free Cash Flow (X2), and Operating Cash Flow (X3) and the dependent variable in this study is Cash Dividend (Y). The results of the study and discussion show that in partial testing (t-test), obtained from the tcount for Net Profit of 2.727 and tcount for Free Cash Flow of 2.086 is greater than the table of 1.989. For Operating Cash Flow variable has no influence on Cash Dividends. The assessment can be seen from the tcount for Operating Cash Flow of -1.201 smaller than t table 1.989. Whereas in simultaneous testing (F test), Net Profit (X1), Free Cash Flow (X2) and Operating Cash Flow (X3) simultaneously affect Cash Dividends. The coefficient of determination obtained by 16%, while the remaining 84% is influenced by other factors ignored by the writer in this study.